Prison and mental health: A brief look at health policy in the context of penal enforcement - Faceira, Lobelia da Silva; Azevedo, Thais de Oliveira; Moura , Sara Cristina da Silva; Andrade, Agnes Conceição Pereira de (Seven Editora, 2023)
The article was produced from the studies and analysis of the research "Social Policies and Prison: an evaluation of the penal execution policy", linked to the Graduate Program in Social Memory and the Social Work Course of the Federal University of the State of Rio de Janeiro (UNIRIO). The article aims to analyze the processes of annulment of subjectivity and illness from the perspective of mental health of individuals deprived of liberty. Incarceration, removal of family and community ties, leisure, loss of autonomy over aspects of everyday life and the unhealthy prison environment are elements that contribute to the degradation of the mental health of inmates. Studies show that people deprived of liberty are more affected by mental disorders than the general population significantly. Therefore, the article presents an analysis of these issues and also of health policy in the scope of criminal enforcement. DOI:https://doi.org/10.56238/interdiinovationscrese-027